Sex differences in methamphetamine pharmacokinetics in adult rats and its transfer to pups through the placental membrane and breast milk - Rambousek, Lukas; Kacer, Petr; Syslova, Kamila; Bumba, Jakub; Bubenikova-Valesova, Vera; Slamberova, Romana (Drug and alcohol dependence, 2014)
BACKGROUND: Methamphetamine (METH) abuse is a growing health problem worldwide, and METH use during pregnancy not only endangers the mother's health but also the developing fetus. To provide better insight into these risks, we performed the following experiments. METHOD: First, we investigated how sex influences the pharmacokinetics of METH and amphetamine (AMP) in male and female rats. Subsequently, we simulated chronic exposure of prenatal infants to METH abuse by investigating brain and plasma levels of METH and AMP in dams and pups. Finally, we modeled chronic exposure of infants to METH via breast milk and investigated sex differences in pups with regard to drug levels and possible sensitization effect of chronic prenatal METH co-treatment. RESULTS: We observed significantly higher levels of METH and AMP in the plasma and brain of female rats compared to males. Additionally, brain concentrations of METH and AMP in pups exposed to METH prenatally were equivalent to 62.13% and 37.78% relative to dam, respectively. Plasma concentrations of AMP where equivalent to 100% of the concentration in dams, while METH was equivalent to only 36.98%. Finally, we did not observe a significant effect relative to sex with regard to METH/AMP levels or sensitization effects linked to prenatal METH exposure. CONCLUSION: We demonstrated that female rats display higher levels of METH and AMP, thus indicating a greater risk of addiction and toxicity. Furthermore, our data show that pups are exposed to both METH and AMP following dam exposure.
Keywords: Placenta; těhotenství; methamfetamin; zvířata; Milk; Rats; zpožděný efekt prenatální expozice; Sex Characteristics; placenta; Brain Chemistry; amfetamin; mužské pohlaví; mozek - chemie; Amphetamine; Methamphetamine; Rats, Wistar; Prenatal Exposure Delayed Effects; krysa rodu Rattus; ženské pohlaví; potkani Wistar; Animals; mléko; Pregnancy; stimulanty centrálního nervového systému; Male; pohlavní dimorfismus; Central Nervous System Stimulants; Female